Overview and prospect of 5G security - Zhiqiang YANG; Li SU; Minpeng QI; Bo YANG (Dianxin kexue)
From 4G to 5G,as the result of network evolution and service promotion,the concepts and principles of security in design were deeply integrated,the security capabilities were enhanced.The root of 5G security design-building secure networks and services in the open environment were analyzed.Furthermore,according to the understanding of the 5G security specifications designed by 3GPP,ITU and GSMA,the security framework and these new technologies were analyzed in detail from three aspects:network security assurance,service security capabilities and security assessment methodologies.The overview of 5G security trends and the key works in the long run were summarized.